Sustainable Innovations in CSR for the Less Privileged - R.S.Rama Rao; Rao, K.S.Sekhara (International Journal of Psychosocial Rehabilitation, 2020)
Corporate Social Responsibility is a much talked about subject in India especially after enactment of Companies Act, 2013. The underlying motive is that Corporate Companies must give back something to society as their very existence is dependent on the services they get from the society. CSR is not only about providing furniture to schools or installation of some RO plants, laying of few roads etc.. The CSR activities should be able to create long lasting impacts, bring changes in the quality of life of citizens. To achieve this objective there is need to focus on innovative CSR programmes. The innovative approaches in CSR should focus more on preservation of ecology and environment, employment generation, empowerment, of women and the marginalized groups. Special attention needs to be given to differently abled persons. The very purpose of CSR philosophy is to touch the lives people in their environment. In order to achieve this objective, the Corporates shall carry out their CSR activities directly in co-ordination with the local communities. The Corporate Companies may consider funding innovative programmes like providing Bike Ambulances in remote and tribal areas, low cost Sanitary Napkin making units, Artificial Limbs, wheel chairs in government hospitals, bus and railway stations and other public places. Innovatively, the corporates, wherever feasible, shall join hands together and take up projects jointly for creating bigger impact.This literature review focuses on CSR programmes being implements by various corporate companies in India, shortcomings and the need for undertaking innovative and sustainable CSR programmes.